A comparative study of finite element modeling techniques for dynamic analysis of elastic-viscoelastic-elastic sandwich structures. (September 2016) - Huang, Zhicheng; Qin, Zhaoye; Chu, Fulei
Two finite element formulations using different laminate plate theories are developed for the elastic-viscoelastic-elastic sandwich plates. A critical comparison and assessment between them are provided. The dynamic characteristics, namely, the natural frequencies and associated loss factors of the elastic-viscoelastic-elastic sandwich plates are calculated using the two finite element models. The two models are validated through the numerical example and experiment results. Comparisons of the accuracy and computational efficiency of the two finite element models are given. The results show that both of the two finite element models have good accuracy in predicting the natural frequencies and the loss factors with different efficiency. The works in this article have instructive significance in the calculation and application of the elastic-viscoelastic-elastic sandwich structures.